2012
DOI: 10.1111/j.1939-0025.2012.01171.x
|View full text |Cite
|
Sign up to set email alerts
|

Potential treatment mechanisms of counseling for children in Burundi: A series of n = 1 studies.

Abstract: Little is known about the impact and treatment processes of psychosocial counseling in low-income countries. This study aimed to generate hypotheses on key working mechanisms of counseling in Burundi. The authors carried out 11 empirically grounded n=1 studies with children (11-14years) screened for depression and anxiety who received counseling. The authors used quantitative (symptom scales) and qualitative instruments (treatment content and perceptions). Weekly measurements were taken preintervention (4 time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(40 citation statements)
references
References 40 publications
0
40
0
Order By: Relevance
“…Interrater reliability for visual inspection (κ = 0.981) indicated a high level of agreement. Similar procedures have been utilized in evaluations of novel interventions in resource‐strained, global mental health settings (e.g., Jordans et al., ; Jordans, Komproe, Tol, Nsereko, & De Jong, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interrater reliability for visual inspection (κ = 0.981) indicated a high level of agreement. Similar procedures have been utilized in evaluations of novel interventions in resource‐strained, global mental health settings (e.g., Jordans et al., ; Jordans, Komproe, Tol, Nsereko, & De Jong, ).…”
Section: Methodsmentioning
confidence: 99%
“…(a) change in trend or symptom level across phases A, B, and follow-up; (b) the degree of change (slope of the graph) between phases; and (c) changes in variability of the data that capture stability of symptom change within phases.Interrater reliability for visual inspection ( = 0.981) indicated a high level of agreement. Similar procedures have been utilized in evaluations of novel interventions in resource-strained, global mental health settings (e.g.,Jordans et al, 2012;Jordans, Komproe, Tol, Nsereko, & De Jong, 2013).…”
mentioning
confidence: 99%
“…We learned that counselor performance was highly stable (i.e., there were counselors with consistently positive results and counselors with consistently negative results), which reemphasized the importance of our clinical supervision and evaluation mechanisms, for example, for early identification of counselors performing poorly. Furthermore, results showed that the combination of universal treatment variables (therapeutic alliance and trust, and a non-moralistic and non-normative counselor) with specific treatment components (active problem-solving, narrative exposure, and cognitive restructuring) was associated with positive client trajectories [21]. These findings resulted in changes in the training curricula and led to the exploration of a components-based intervention approach.…”
Section: Impact and Barriers: The Interplay Between Practice And Resementioning
confidence: 99%
“…We conclude with recommendations to improve future uptake of psychosocial and mental health care. While several articles have been published on separate studies of the program [13],[16][21], we have thus far not provided an integrated overview of the overarching lessons learned through research and practice reflections.…”
Section: Introductionmentioning
confidence: 99%
“…A good example of this is N = 1 single case studies in which outcome variables are measured at various points in a lead‐up to an intervention, during, and after. This helps determine when changes occur and what the active ingredients in an intervention are (Jordans et al, ).…”
Section: Human Biology Framework For Intervention Development and Impmentioning
confidence: 99%